Ionic liquids uncoiled critical expert overviews - Plechkova, Natalia V.; Seddon, Kenneth R., 1950- (Hoboken, New Jersey : John Wiley & Sons, 2012)
"The book presents articles on topics at the forefront of ionic liquids research range from applied to theoretical, from synthetic to analytical, from biotechnology to electrochemistry, from process engineering to nanotechnology"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Ionic solutions; Ionic structure; SCIENCE -- Chemistry -- Physical & Theoretical; Ionic solutions; Ionic structure; Electronic books; Electronic books